A parametric study on the subharmonic isolas in a bistable dielectric elastomer actuator. (1st December 2022) - Cao, Chongjing; Chen, Lijin; Hill, Thomas L; Wang, Lei; Gao, Xing
Abstract: Resonant actuation of dielectric elastomer actuators (DEAs) greatly improves their output power densities and energy efficiencies. However, their outstanding performance usually accompanies complex dynamics which hinder the robust applications of DEAs. Isolated frequency responses, or isolas, are branches of resonant curves that are isolated from the main frequency response curve, hence can be easily overlooked during the dynamic analyses of DEAs. Once triggered, however, isolas can lead to dramatic changes in frequency responses, which pose great threats to system stability. As a critical step towards controlling the isolas within DEAs, this work adopts a bistable cone DEA (BCDEA) configuration and conducts dedicated numerical and experimental parametric studies on its isolas to uncover the physical mechanisms that create them. The effects of potential barriers, equilibrium positions and excitation level on the evolutions of isolas are studied with the aim of finding the critical parameters that determine their evolutions. The outcomes of this paper help to gain more insights into the complex isola phenomena in BCDEAs, which may offer guidelines for eliminating undesired isolas within BCDEAs or for exploiting isolas for applications in, e.g. energy harvesting, soft robotic locomotion and vibro-tactile feedbacks.